Partisipasi Perempuan dan Pemberdayaan Masyarakat di Objek Wisata Pulau Banyak Aceh Singkil - Sopar Sopar; Mursyidin Mursyidin; Arfriani Maifizar; Riki Yulianda; Rahmah Husna Yana (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
Several tourist attractions in Indonesia have involved local communities in their management and development. Community empowerment strategies include human resource development, productive endeavors, provision of information, capital development, and group institutionalization. This article focuses on women's participation in the empowerment of coastal communities in the tourist attraction of Pulau Banyak, Aceh Singkil. The objective of this article is to describe women's participation, forms of empowerment, and inhibiting factors. This study is based on qualitative field research to be conducted in 2022. Data was collected through in-depth interviews with relevant informants. The study showed that, in addition to the economic potential of marine and fisheries resources, Pulau Banyak also possesses promising tourism potential due to its attractive natural landscapes. This tourism potential has been utilized by the local community and women through microeconomic activities. However, women's empowerment strategies in the context of tourism on Pulau Banyak are still limited and rely on government assistance. Insufficient mentoring and limited marketing access are obstacles to women's empowerment. Abstrak Beberapa objek wisata di Indonesia telah melibatkan masyarakat lokal dalam pengelolaan dan pengembangan. Strategi pemberdayaan masyarakat termasuk pengembangan sumber daya manusia, usaha produktif, penyediaan informasi, pengembangan modal, dan kelembagaan kelompok. Artikel ini fokus pada partisipasi perempuan dalam pemberdayaan masyarakat pesisir di objek wisata Pulau Banyak, Aceh Singkil. Tujuan artikel ini adalah mendeskripsikan partisipasi perempuan, bentuk pemberdayaan, dan faktor penghambatnya. Kajian ini didasarkan pada penelitian lapangan dengan pendekatan kualitatif yang dilakukan pada tahun 2022. Data dikumpulkan melalui wawancara mendalam dengan informan terkait. Kajian ini menunjukkan bahwa selain potensi ekonomi dari hasil kelautan dan perikanan, Pulau Banyak juga memiliki potensi wisata yang menjanjikan karena panorama alamnya yang menarik. Potensi wisata tersebut telah dimanfaatkan oleh masyarakat dan kaum perempuan dalam bentuk aktivitas ekonomi mikro, Namun, strategi pemberdayaan perempuan dalam konteks wisata di pulau banyak masih terbatas dan bergantung pada bantuan pemerintah. Kurangnya pendampingan dan akses pemasaran yang terbatas menjadi kendala dalam pemberdayaan perempuan.